Penerapan Problem Based Learning dalam Penelitian Tindakan Kelas Untuk Meningkatkan Motivasi dan Hasil Belajar Biologi Pada Peserta Didik Kelas X SMA Negeri 3 Palu - Sari, Maya; Tangge, Lilies; Mahyuddin, Mahyuddin (Green Publisher Indonesia, 2025)
This research aims to improve the motivation and learning outcomes of Biology through the application of the Problem Based Learning (PBL) learning model in class X students of SMA Negeri 3 Palu. The type of research used is Class Action Research (PTK) which is carried out in two cycles with four stages: planning, implementation, observation, and reflection. The research subjects consisted of 35 students in classes X-L. Data were collected using learning motivation questionnaires and learning outcome tests, then analyzed in a quantitative descriptive manner. The results showed that the application of PBL can increase students' motivation to learn, most of which are in the categories of high motivation (63.6%–80.4%) and very high (81.4%–100%). In addition, student learning outcomes also increased, with an average score from 66 in the first cycle to 81.29 in the second cycle, and classical completeness increased from 28.6% to 85.71%. Thus, the application of PBL has been proven to be effective in increasing the motivation and learning outcomes of Biology students in class X of SMA Negeri 3 Palu.